Evolutionary trajectories of IDH-mutant astrocytoma identify molecular grading markers related to cell cycling - Vallentgoed, Wies; Hoogstrate, Youri; van Garderen, Karin A.; van Hijfte, Levi; van Dijk, Erik; Kouwenhoven, Mathilde C. M.; Niers, Johanna M.; Draaisma, Kaspar; Martin, Ivonne; de Leng, Wendy W. J.; Tesileanu, C. Mircea S.; de Heer, Iris; et al. (Nature cancer, 2025)
The evolutionary processes that drive malignant progression of IDH-mutant astrocytomas remain unclear. Here, we performed multiomics on matched initial and recurrent tumor samples from a cohort of 105 patients and overlaid the data with detailed clinical annotation. We identified overlapping features associated with malignant progression that are derived from three molecular mechanisms: cell cycling, tumor cell (de)differentiation and remodeling of the extracellular matrix. Together, they provide a rationale of the underlying biology of tumor malignancy. DNA methylation levels decreased over time, predominantly in tumors with malignant transformation, and co-occurred with poor prognostic genetic events. We identified a DNA methylation-based signature strongly associated with survival, which allows objective, molecular-based grading of IDH-mutant astrocytomas to aid clinical decision making. Our findings were validated on large, independent cohorts of IDH-mutant astrocytoma samples. Lastly, in this retrospective study, we found little effect of radiotherapy or chemotherapy on the molecular features associated with malignant progression.
Online veröffentlicht: 19. August 2025
Gesehen am 21.01.2026